Fighting poverty with microcredit : experience in Bangladesh - Khandker, Shahidur R.; World Bank. (Oxford : Oxford University Press, 1998)
Providing microcredit to the poor has become an important antipoverty scheme in many countries. Microcredit helps the poor become self-employed and thus generates income and reduces poverty. Are these programs cost-effective? This book addresses the question, drawing on the experiences of the well-known microcredit programs of Bangladesh's Grameen Bank, the Rural Development-12 project, and the Bangladesh Rural Advancement Committee. It examines the cost-effectiveness of microcredit programs vis-a-vis other antipoverty programs, such as Food-for-Work.
1. Poverty Alleviation and Microcredit Programs -- 2. The Evolution of Microcredit Programs in Bangladesh -- 3. Socioeconomic Impacts of Microcredit Programs -- 4. Growth Potential of Activities Financed through Microcredit -- 5. Institutional and Financial Viability of Microcredit Programs -- 6. Microcredit Programs and Rural Financial Markets -- 7. Cost-Effectiveness of Alternative Poverty Alleviation Programs -- 8. Conclusions and Policy Implications: What Have We Learned? -- App. A. Statistical Tables -- App. B. Description of the Sample Used in the Bangladesh Institute of Development Studies-World Bank 1991/92 Survey -- App. C. Evaluating Microcredit Programs -- App. D. Resolving the Problem of Endogeneity in Estimating the Impact of Credit.
Published for the World Bank.
Includes bibliographical references (p. 209-217) and index.
Keywords: Microfinance -- Bangladesh; Microfinance